Ecotoxicity and Biodegradability of Oxytetracycline and Ciprofloxacin on Terrestrial and Aquatic Media - Cláudio Ernesto Taveira Parente; Jordi Sierra; Esther Martí (Orbital: The Electronic Journal of Chemistry, 2018)
Antibiotics are widely found in the environment. For this work, two antibiotics were chosen: oxytetracycline (OTC), used for human and veterinary purposes, and ciprofloxacin (CIP), prescribed for human medicine. The aim of this study was to assess ecotoxicological effects under standardizes methods and the biodegradability in terrestrial and aquatic environments for both molecules. In soil, were tested soil respiration, nitrification, and the growth of Allium cepa L. (onion), Lolium perenne L. (ryegrass) and Raphanus sativus L. (radish). Vibrio fischeri bioluminescence test and BOD (5 and 28 days) were performed in water. Assays were done in concentrations ranging 0.1, 1, 10, 100, 1,000, 5,000 and 10,000 mg.kg-1/ mg.L-1. Biodegradability was determined by HPLC/UV in the soil and water. OTC was more persistent in water while CIP better persisted in soil. Both antibiotics elicited negative effects on nitrification at highest doses, whereas CIP produced slight inhibition on soil respiration. Lowest values for EC50 plants growth were: 10 mg.kg-1 (CIP) for A. cepa (root) and 40 mg.kg-1 (OTC) for R. sativus (stem). CIP stimulated R. sativus root growth with 1 mg.kg-1 and was harmless to L. perenne. This work contributes to increasing knowledge about the toxicity and biodegradability of OTC and CIP for some trophic levels in terrestrial and aquatic media.DOI: http://dx.doi.org/10.17807/orbital.v10i4.1063